2016
DOI: 10.1016/j.slsci.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Case comparison of sleep features from ear-EEG and scalp-EEG

Abstract: BackgroundWe investigate the potential usability of a novel in-the-ear electroencephalography recording device for sleep staging.MethodsIn one healthy subject we compare simultaneous earelectroencephalography to standard scalp EEG visually and using power spectrograms. Hypnograms independently derived from the records are compared.ResultsWe find that alpha activity, K complexes, sleep spindles and slow wave sleep can be visually distinguished using earelectroencephalography. Spectral peaks are shared between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 8 publications
3
42
0
Order By: Relevance
“…As illustrated in Figure 7, different EEG sleep features comprising theta activity, k-complexes and slow wave sleep could be captured with the cEEGrid. Compared to in-ear EEG (Zibrandtsen et al, 2016) the cEEGrid ear-EEG amplitudes are somewhat larger.…”
Section: Sleep Stagingmentioning
confidence: 87%
See 2 more Smart Citations
“…As illustrated in Figure 7, different EEG sleep features comprising theta activity, k-complexes and slow wave sleep could be captured with the cEEGrid. Compared to in-ear EEG (Zibrandtsen et al, 2016) the cEEGrid ear-EEG amplitudes are somewhat larger.…”
Section: Sleep Stagingmentioning
confidence: 87%
“…Traditional sleep EEG recordings use bipolar derivations between a mastoid and a central location (e.g., C4, Campbell, 2009). Recently, Zibrandtsen et al (2016) reported a first case study of sleep staging using ear-EEG and compared ear-EEG and cap-EEG. Although the amplitudes of the ear-EEG recordings were considerably smaller when compared to those derived from cap-EEG channels, ear-EEG may allow for an identification of sleep stages (see also Stochholm et al, 2016).…”
Section: Sleep Stagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The ear-EEG could most likely be utilized for the majority of the clinical and research applications mentioned above. This includes more specific applications, such as sleep diagnostics [106], monitoring of impending severe hypoglycemia (SH, insulin shock) in insulin-treated diabetics [53] and monitoring of frequency and length of seizures in childhood absence epilepsy [36]. Studies show that impending SH can be observed in the EEG, and a device enabling constant monitoring of EEG in the everyday life could effectively alarm about an impending SH [53,93].…”
Section: Motivationmentioning
confidence: 99%
“…Other applications of ear-EEG, which is currently being explored, include sleep stage classification [106] and monitoring of epilepsy. 15 patients under clinical investigations for epilepsy, have been monitored with ear-EEG in an epilepsy monitoring unit at Roskilde Hospital.…”
Section: Perspectivesmentioning
confidence: 99%